STRATEGI GURU PAI DALAM MENANGANI KONFLIK SOSIAL ANTAR SISWA DI SDN 2 LINGGASARI DARANG DAN PURWAKARTA - Indriani, Dini; Iwan Hermawan; Nia Karnia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the strategies of Islamic Religious Education (PAI) teachers in handling social conflicts among students in the classroom. The research employed a descriptive qualitative approach, with data collected through observation and interviews. The subject of this study was a PAI teacher at SDN 2 Linggasari Darang dan Purwakarta. The findings indicate that social conflicts among students are generally caused by personal factors such as teasing, differences of opinion, and competition. The strategies used by PAI teachers include religious approaches, mediation through open dialogue, personal approaches, and the habituation of good moral values in daily activities. These strategies are not only reactive but also preventive and educative in shaping students’ character. Therefore, the role of PAI teachers is crucial in creating a harmonious and conducive classroom environment through the internalization of Islamic values. Keywords: PAI teacher strategies, social conflict, students, character education.